Tata Kelola Keuangan Desa dan Kompetensi Aparatur: Implementasi SISKEUDES Berdasarkan Permendagri Nomor 20 Tahun 2018 - Marcella Aullia Jayadi; Tries Ellia Sandari (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines village financial governance and the competence of village officials in implementing the Village Financial System (SISKEUDES) based on the Indonesian Minister of Home Affairs Regulation Number 20 of 2018. Using a qualitative descriptive approach, the research focuses on how human resource capacity and task distribution influence the effectiveness of SISKEUDES implementation. The findings indicate that although the application has supported orderly budgeting, administration, and reporting, operational practices remain highly dependent on the village financial officer as the main system operator. Village heads and secretaries generally understand financial procedures conceptually but lack sufficient technical skills to operate SISKEUDES independently. This imbalance creates administrative vulnerability, particularly during periods of high workload or technical disruption. The study also shows that limited competency distribution affects accountability, efficiency, and continuity of village financial management. Strengthening technical capacity across officials, improving internal coordination, and optimizing task allocation are essential to enhance SISKEUDES performance. Efective implementation of SISKEUDES requires not only regulatory compliance but also sustainable human resource development to ensure transparent, accountable, and resilient village financial governance..